Extracorporeal cardiopulmonary resuscitation in children after open heart surgery. Issue 7 (14th January 2019) - Guo, Zheng; Yang, Yinyu; Zhang, Wei; Shen, Jia; Jiang, Lei; Yu, Xindi; Wang, Wei
Abstract: Extracorporeal membrane oxygenation (ECMO) provides cardiorespiratory support during cardiopulmonary resuscitation unresponsive to conventional methods. Here, we analyzed the extracorporeal cardiopulmonary resuscitation (ECPR) results of children in a cardiac arrest setting after cardiac surgery. Of 3119 cases of pediatric open‐heart surgery, 31 required postoperative ECMO. Among the 31 patients, 11 experienced cardiac arrest and ECPR in the early postoperative period. These 11 patients' median age is 1.5 [range, 0.1‐19] months and median weight is 3.9 [range, 2.9‐10.3] kg. The medical records of ECPR cases were analyzed. The median ECMO‐assisted time was 68 (range, 13‐456) hours and 4 cases (36.4%) survived. The ECMO‐assisted times were ≤2 days in 4 patients (all eventually died), ≥6 days in 3 patients (all also died), and all 4 cases supported for 2‐6 days were discharged successfully ( P = 0.006). In the survivors and nonsurvivors, peak lactate levels were 10.8 ± 7.04 and 22.8 ± 6.98 mmol/L ( P = 0.023) and peak creatinine levels were 47.50 ± 25.9 and 153.7 ± 73.9 mg/dL ( P = 0.035), respectively. In these 11 ECPR cases, the most common complications were bleeding requiring re‐exploration ( n = 6, 54.5%) and renal failure ( n = 6, 54.5%). The incidence of renal failure was significantly correlated with hypoperfusion time ( P = 0.015). ECPR is valuable in children with postoperative cardiac arrest. The higher peak lactate level, higher peak creatinine level, and prolonged ECMO duration were associated with higher mortality. Early diagnosis and intervention of residual anatomical problems could improve survival. Bleeding and renal failure were the most common complications and the incidence of renal failure may be correlated with longer hypoperfusion duration.